Delongia gen. nov., a new genus of Polytrichaceae (Bryophyta) with two disjunct species in East Africa and the Himalaya - Bell, N.E.; Kariyawasam, I.U.; Hedderson, T.A.J.; Hyvonen, J. (TAXON, 2015)
Attached

A lthough the fam ily P olytrichaceae co n tain s th e largest and stru c tu ra lly m ost com plex o f all m osses, a n u m b er o f d istan tly related lineages share a relatively red u ced gam etophytic m orphology an d have h isto rically been co n fla te d u n d er polyphyletic genera, m o st notably Oligotrichum s.l. B ased on new an d new ly id en tified collections, phylogenetic analysis o f nucleotide d ata, scan n in g electro n m icroscopy and relaxed-clock divergence tim e estim atio n , w e reco g n ise O. glaciate an d O. cavallii u n d e r th e new g enus Delongia, w h ic h is m ore closely related to Psilopilum, Atrichum an d Steereobryon than to Oligotrichum. T h e tw o species are m u tu ally h ig h ly d istin c t in bo th m orphological an d ’m olecular ch aracters, w ith D. glacialis o ccu rrin g across th e H im alaya fro m P ak istan to Y u n n an and D. cavallii found in th e E ast A fric a n R ift M ountains and on the islan d o f R eunion. D ivergence tim e estim ation su g g ests th at th e lineages rep resen ted by th e ex tan t species diverged from each o th er around the O ligocene-M iocene b o u n d ary (~23 M a), contem poraneous w ith th e o rigins o f th e E ast A frican R ift system and ongoing u p lift o f the Q inghai-T ibetan Plateau, w h ile Delongia m o st likely sh ares a com m on an cesto r in the E ocene (56-34 M a) e ith er w ith the arctic-su b arctic g enus Psilopilum o r w ith Atrichum and Steereobryon.
Keywords: bryophyte phytogeny; East African Rift; mosses; Oligotrichum; relaxed-clock dating; Reunion